DEVELOPING AND VALIDATING A TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) INSTRUMENT FOR SECONDARY PHYSICS PRESERVICE TEACHERS IN INDONESIA - Hidayat, Arif (Unnes Science Education Journal, 2019)
The purpose of this study is to develop and validate an instrument for assessing secondary pre-service physics teachers’ TPACK in technology – supported classroom environments. In order to achieve the purpose, a total of 116 items with a 6–point Likert type scale in 7 domains with 18 items in Content Knowledge (CK), 32 items in Pedagogy Knowledge (PK), 14 items in Technological Knowledge (TK), 20 items in Pedagogical Content Knowledge (PCK), 9 items in Technological Content Knowledge (TCK), 10 items in Technological Pedagogical Knowledge (TPK), and 13 items in Technological Pedagogical Content Knowledge (TPACK) were developed for the instrument. Theoretical framework of survey development process and results from a pilot study on 1005 pre-service and in-service science teachers would be discussed. The construct validity of this instrument was examined through confirmatory factor analysis using principal axis factor (PFA), and multiple PFA method are applied after selecting items without sharing of factor loading to ensure there is no ambiguous of items respective to the formed factors. In terms of those applied, the result shows after the modification and/or deletion of 66 of the survey items, the 50 items-survey is a reliable and valid instrument that will help educators design longitudinal studies to assess physics preservice teachers’ development of TPACK.